A new species of Alopecosa Simon, 1885 (Araneae, Lycosidae) from the Altai Mountains (South Siberia, Russia) - Fomichev, Alexander A.; Logunov, Dmitri V. (Zootaxa, 2015)
Alopecosa Simon, 1885 is a large genus of wolf spiders containing more than 166 named species (World Spider Catalog 2015), of which 81 valid species have been recorded from the territory of ex-USSR (Mikhailov 2013). In the mountains of South Siberia, to which the Altai Mts belong, 35 species of Alopecosa have been recorded to date (Mikhailov 2013), but findings of some of them require confirmation upon reference to the pertinent material. Yet, some authors (e.g., Marusik & Kovblyuk 2011) argue that the genus Alopecosa is a paraphyletic taxon that needs to be split up into a number of separate genera.